NEW UPPER PERMIAN SUPERFAMILY COMPOSITELASMATOIDEA (BRACHIOPODA, TEREBRATULIDA) FROM THE EAST OF THE RUSSIAN PLATFORM: THE SPECIFICITY OF ONTOGENETIC TRANSFORMATIONS - Smirnova T.N. (My University, 2006)
A previously unknown type of ontogeny is discussed that unites features of two different types of loop development: the ancient dielasmoid type, which is typical of Upper Paleozoic terebratulids, and the angustothyridid type, which is typical of the Lower Mesozoic terebratulids. A new superfamily, Compositelasmatoidea, and a new family, Compositelasmatidae, with its type genus Compositelasma gen. nov., are established based on their unique ontogenetic changes. © Pleiades Publishing, Inc. 2006.
Keywords: CHUVASHSKII BAITUGAN; LOWER KAZANIAN SUBSTAGE; RUSSIAN PLATFORM; SOK RIVER; UPPER PERMIAN; Guadalupian; Paleozoic::Permian::Guadalupian; Палеозой::Пермская::Гваделупский